Influence of L-Arginine on the growth of potassium sulphate single crystal. (2021) - Anitha, M.; Ravindran, B.; Vijayalakshmi, M.
Abstract: Potassium Sulphate doped with L-Arginine crystals were grown and harvested successfully by utilizing solution slow evaporation growth process under normal room temperature. Using different analysis techniques the grown PSLA crystals were characterized. Some of the studies such as TGA-DSC, UV–Vis-NIR., FTIR, and NLO, etc., were used to confirm the grown crystal. Functional group presence and the metal ion co-ordination were confirmed by Fourier Transform Infra-Red spectroscopic analysis. The spectrum of transmission reveals about the low wavelength cut-off of the grown crystal lies at 230 nm and confirms the high transparency in the entire ultraviolet, range of visibility, and far-infrared range reveals about the utilization in the field of optical applications. The behavior of the crystal concerning the thermal approach was investigated using the DSC (Differential Scanning Calorimetric) analysis and TGA (Thermo Gravimetric analysis) and found to be recorded as the stability enhanced up to 250 °C. Conversion of optical second-harmonic efficiency of the harvested material using Kurtz technique (powder) methodology made a record of 4 mV output.